Pengaruh Kombinasi Pupuk Hayati Mikoriza dan Dolomit terhadap Pertumbuhan Tanaman Kelapa Sawit (Elaeis guineensis Jack) TBM 1 - Rio Andika; Subagiono (Jurnal Greenation Pertanian dan Perkebunan, 2026)
This study aims to determine the effect of the combination of mycorrhizal and dolomite biofertilizers on the high growth of oil palm plants (Elaeis guineensis Jacq.) in the Unyielding Crops (TBM) phase 1. This research was carried out in Rantau Keloyang village, Pelepat District, Bungo Regency, Jambi Province, namely at an altitude of ± 120 m above sea level with a pH of 4.8 in the Ultisol type, this research was carried out on May 26 - August 10, 2025. This study used a randomized design of a non-factorial group with five treatments, namely M0 (100 g mycorrhiza), M1 (30 g mycorrhizah + 650 g dolomite), M2 (80 g mycorrhizah + 550 g dolomite), M3 (130 g mycorrhizah + 450 g dolomite), and M4 (180 g mycorrhizae + 350 g dolomite), each repeated three times. The observation variables were the increase in the height of the oil palm plant (cm), the increase in the trunk circumference (cm), the increase in the area of the leaves (cm2), and the increase in the number of fronds (fruit). To see the effect of the combination of treatments on the observation variables, the data obtained was statistically analyzed with various fingerprints, if it had a real effect, it was followed by the DNMRT test at the level of 5%. The results of the variety-analysis showed that the application of a combination of mycorrhizal and dolomite had a very significant effect on the growth of TBM 1 oil palm. The M0 treatment provided the best growth with an average height increase of 10.57 cm, followed by an increase in stem circumference, leaf area, and better fronds count compared to the mycorrhiza dolomite combination treatment. The growth pattern shows an upward trend over time with clear growth points on the 30th, 60th, and 70th days. These results indicate that the application of a single mycorrhizal is more effective in supporting the vegetative growth of oil palm TBM 1 compared to the combination with dolomite